Hubungan Antara Kualitas Pertemanan dengan Subjective Well-Being Remaja - Amanda Elizafitriani; Nurwahyuni Nasir; Hema Dayita (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study aims to examine the relationship between friendship quality and subjective well-being among adolescents in Bekasi Regency. Adolescence is a developmental stage characterized by significant physical, emotional, social, and psychological changes that may influence an individual's well-being. During this period, friendships play an important role in adolescents’ lives, as peers often serve as sources of support, companionship, and acceptance. Subjective well-being refers to an individual’s evaluation of their life, including life satisfaction, positive affect, and negative affect. Friendship quality, on the other hand, refers to the degree of closeness, trust, support, security, and comfort experienced within a friendship.This study employed a quantitative correlational approach to investigate the relationship between these variables. The participants consisted of 140 adolescents aged 14–17 years living in Bekasi Regency, selected using an incidental sampling technique. Data were collected using three instruments: the Satisfaction with Life Scale (SWLS), the Scale of Positive and Negative Experience (SPANE), and the Friendship Quality Scale (FQS). The collected data were analyzed using correlation analysis to determine the strength and direction of the relationship between friendship quality and subjective well-being.The results revealed a significant positive relationship between friendship quality and subjective well-being among adolescents. These findings indicate that adolescents who experience higher-quality friendships tend to report higher levels of subjective well-being. Positive friendship quality provides emotional support, a sense of comfort, and enjoyable social experiences, which contribute to enhancing adolescents’ overall well-being. Therefore, friendship quality can be considered an important factor in promoting subjective well-being among adolescents.